Reading deconstruction : deconstructive reading - Atkins, G. Douglas (George Douglas), 1943- (The University Press of Kentucky, 2015)
Deconstruction -- a mode of close reading associated with the contemporary philosopher Jacques Derrida and other members of the ""Yale School""--Is the current critical rage, and is likely to remain so for some time. Reading Deconstruction / Deconstructive Reading offers a unique, informed, and badly needed introduction to this important movement, written by one of its most sensitive and lucid practitioners. More than an introduction, this book makes a significant addition to the current debate in critical theory. G. Douglas Atkins first analyzes and explains deconstruction theory and practi